Pelatihan Bahasa Arab : Mufrodat A’dho’ul Jismi dengan Metode Interaktif pada Anak-Anak di Majlis Darul Anwar kp. Sukajaga Desa Cihanjawar - Yayu Wahyudah; Rohendi Rohendi; Abdurrahman Shaleh (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2025)
The Arabic language training using an interactive learning method at Majelis Darul Anwar Kampung Sukajaga aimed to enhance children’s vocabulary in Arabic, particularly concerning body parts (a'dho'ul jismi). The method emphasizes active involvement of children through games and participatory activities, such as the "Point to the Body Parts" game in Arabic. Observational results showed that most children had limited understanding of Arabic vocabulary prior to the training; however, after participating, they became more active and motivated to learn. Additionally, they were able to recall and apply the vocabulary in real-life situations. This training is expected to make a positive contribution to improving Arabic language learning among children and motivate them to further develop their Arabic skills. The sustainability of this program requires periodic evaluations and parental support to ensure consistent learning outside the classroom. Therefore, this training has the potential to strengthen children’s understanding of Arabic as part of the development of Islamic education.